Footwear buying needs and considerations of selected transgender women - Santos, Patrick Andre Chin (College of Home Economics, University of the Philippines Diliman, 2021)
Adequate access to clothing and footwear is one of the concerns transgender women face as one of the most marginalized sectors in society. This study analyzed the needs of transgender women in buying footwear using The Functional, Expressive and Aesthetic Model (Lamb & Kallal, 1992) as applied in product development (Bye & Hakala, 2005; Black & Stokes, 2012). Data was collected using an online questionnaire from 114 self-identified transgender women. The parameters for functional need considerations were type of footwear, size, fit and comfortability, quality and wearability. For expressive needs, the considerations identified were femininity, masculinity, help in transition, and help to pass. Meanwhile, personal style and attractive appearance were identified as aesthetic need considerations. Results show that respondents buy all types of footwear subjects of the study with considerations on functional, expressive, and aesthetic factors. However, masculinity was only considered in buying walking shoes, high heels, thongs, slippers, backless slippers, court shoes, mules and sandals. Moreover, availability, sizing, fit and comfortability, quality, femininity, congruence to one’s style, and attractiveness were identified as concerns in buying footwear across all footwear types. While majority (61.4%) of the respondents agreed that there is a need for a transgender women’s footwear brand, it was more of a size concern, and not gender. This study provided recommendations useful in doing a Phase 2 of the study focused on functional concerns as these presented limitations to expressive and aesthetic considerations.